Numerical Design of a Guide Vane for an Axial Fan - Saeidi, Ali; Taheri, Pooya (Applications of Modelling and Simulation, 2020)
This study presents a custom guide vane design to substantially reduce the waste energy in axial fans. Ideally, there is no velocity component in the radial direction in axial fans, but in practice, the air leaving the axial fan has a large tangential component of velocity which produces a large amount of swirl kinetic energy. In order to solve this problem, a guide vane is designed to remove the rotational component of the air. The methodology described in this project is based on the fundamental governing continuity, momentum, and energy equations using the Finite Volume Method (FVM). In this project, the standard k-ω model is used for turbulent modeling. Two dimensional (2D) geometry of blades and airflow cross-section are designed using AutoCAD and CATIA while GAMBIT is employed to generate a suitable mesh for the three dimensional (3D) model. The mesh independence test is done to analyze the performance. The axial fan is simulated using FLUENT software to prove an increase in airflow rate after using the guide vane. Considering the final results, it can be observed that the airflow is increased up to 6.3%.